Cationic Interstitials: An Overlooked Ionic Defect in Memristors - Xu, Zhemi; Guan, Peiyuan; Ji, Tianhao; Hu, Yihong; Li, Zhiwei; Wang, Wenqing; Xu, Nuo (Frontiers in Chemistry, 2022)
Memristors provide solutions for breaking through the limitations in data storage density and efficiency, owing to their great potential in multi-state data storage and neuromorphic computing. Currently, the oxide-based resistive switching behavior is mainly ascribed to the formation and rupture of highly conductive filaments formed by the migration of cations from electrodes or oxygen vacancies in oxides. However, due to the relatively low stability and endurance of cations from electrodes, and the high mobility and weak immunity of oxygen vacancies, such resistive switching can be hardly kept at stable intermediate resistance states for multilevel or synaptic switching. Herein, we reviewed the memristors based on another common ionic defect, cationic interstitial, which has been overlooked in achieving digital resistive switching and synaptic analog switching. Both theoretical calculations and experimental works have been included, which may provide reference and inspiration for the rational design of multifunctional memristors and will promote the increments in memristor fabrications.